Integrative taxonomic revision of the African taxa of the Racotis Moore, 1887 generic complex (Lepidoptera, Geometridae, Ennominae, Boarmiini) - László, Gyula M.; Hausmann, Axel; Karisch, Timm (Zootaxa, 2023)
The Afrotropical taxa of the Racotis s.l. generic complex are revised utilising integrative taxonomical methods. Based on the evaluation of genital morphology and analyses of DNA barcodes, a new genus, Afroracotis gen. n. is established to include the Afrotropical “Racotis” species. The new genus is subdivided into 5 subgenera: Afroracotis subgen. n., Herbuloracotis subgen. n., Rwandaracotis subgen. n., Zebracotis subgen. n. and Sokokeracotis subgen. n.. A new monotypic genus is described to include Boarmia ugandaria Swinhoe, 1904 which was combined earlier with the genus Chorodna and recently with Racotis: Chorocotis gen. n.. Two species formerly assigned to Cleora are moved to Afroracotis: A. albitrigonis (Prout, 1927) comb. n., A. atriclava (Prout, 1926) comb. n.. Two species are transferred from Racotis to Colocleora: C. breijeri (Prout, 1922) comb. n., C. incauta (Prout, 1916) comb. n.. Seventeen new Afroracotis species (A. aliena, A. stadiei, A. violetteae, A. fiebigi, A. turlini, A. dargei, A. longicornuta, A. aristophanousi, A. muscivirens, A. chaineyi, A. lydiae, A. smithi, A. ochsei, A. milesi, A. helicalis, A. takanoi and A. staudei spp. n.) and 5 new subspecies (A. squalida thomensis, A. argillacea morettoi, A. longicornuta congolana, A. longicornuta ugandana and A. lydiae orientalis sspp. n.) are described, totalling 27 species and 8 subspecies contained in the genus Afroracotis. Adults and genitalia of all taxa are illustrated in 210 colour and 129 black and white figures demonstrating the intraspecific variability. The distribution of all taxa is illustrated in 6 dot maps. The results of the genetic analyses are figured in four phylograms.